Portable biogas as alternative energy by utilizing durian peel - Andi Widiyanto; Wahyu Aji Suryantoro; Febri Aris Prasetyo; Hanif Farkhan Naufal; Achmad Rizal Maslikhan; Dimas Istiyadi (Universitas Muhammadiyah Magelang, 2022)
In the Magelang district, Candimulyo is well known as a durian center. During the harvest season, durian peel waste is piled up in several places. Through a portable biogas reactor, this community service attempts to use durian peel waste as an alternative energy source. Participatory Rural Appraisal (PRA) is the methodology employed to incorporate the community's active role in the implementation of program. As a result, portable biogas innovation can be used to light a stove, in an average of 20-40 minutes.